Legal Analysis of the Application of Article 363 of the Criminal Code in the Sekayu District Court Decision Number 70/Pid.B/2021/PN Sky Regarding Theft in a Plantation Area - M. Saleh, Tri Wahyuni; Malik, Faissal; Hasan, Aslan (Candela Edutech Indonesia, 2025)
This study aims to examine the suitability of the indictment with Article 363 paragraph (1) 4 of the Criminal Code used by the Public Prosecutor in decision Number 70/Pid.b/2021/PN Sky and whether the Judge's considerations in decision Number 70/Pi.B/2021/PN Sky were in accordance with the facts of the trial. The type of research used is normative legal research, which is a method of legal research conducted by examining library materials or secondary data. Based on research, it can be seen that there is a discrepancy between the indictment and Article 363 paragraph (1) point 4 of the Criminal Code used by the Public Prosecutor, as well as between the verdict and the judge's consideration, which does not or does not fully correspond with the facts of the trial, so that the article in the Public Prosecutor's indictment is still used. Both prosecutors and judges should apply the principle of lex specialis derogate lex generali in applying articles in indictments and in court decisions, so that justice can truly be upheld.